2022
DOI: 10.1109/jphot.2022.3199908
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Refractive Index Sensor With Ultra-High Sensitivity Based on Sub-Wavelength Grating Racetrack Microring Resonators and Vernier Effect

Abstract: An approach to optimize the sensitivity and the limit of detection of on-chip refractive index sensor is proposed and demonstrated based on sub-wavelength grating racetrack microring resonator and Vernier effect. The sub-wavelength grating waveguide can reduce the structure limitation of the light field, which is beneficial to enhancing the interaction between the photon and analyte. By optimizing the parameters of the subwavelength grating racetrack microring resonator, the sensitivity of the sensor could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The proposed HDSSWG-MRR achieves the highest sensitivity of 1005 nm/RIU to date under the refractive index of the water stop solution, while the sensitivity of most resonant refractive index sensors is less than 500 nm/RIU. Compared with the reported subwavelength grating waveguide refractive index sensors of 664 nm/RIU [ 46 ] and 823 nm/RIU [ 47 ], the sensitivity has been improved by 341 nm/RIU and 182 nm/RIU, respectively, which represents a leap in sensitivity. On the other hand, the designed structure does not require a particularly high machining accuracy.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The proposed HDSSWG-MRR achieves the highest sensitivity of 1005 nm/RIU to date under the refractive index of the water stop solution, while the sensitivity of most resonant refractive index sensors is less than 500 nm/RIU. Compared with the reported subwavelength grating waveguide refractive index sensors of 664 nm/RIU [ 46 ] and 823 nm/RIU [ 47 ], the sensitivity has been improved by 341 nm/RIU and 182 nm/RIU, respectively, which represents a leap in sensitivity. On the other hand, the designed structure does not require a particularly high machining accuracy.…”
Section: Resultsmentioning
confidence: 83%
“…Subsequently, a sensitivity of 490 nm/RIU [ 45 ] and a Q factor of 7000 were achieved through a SWGMRR. By further optimizing the geometric parameters of the SWG waveguide, the sensitivity of 664 nm/RIU [ 46 ] was obtained, and the Q factor was increased to 15,918 by using a retrack SWGMRR. A single slot SWGMRR was proposed, which minimizes the propagation loss of the optical field by designing the inner ring subwavelength grating waveguide block into a trapezoidal shape.…”
Section: Introductionmentioning
confidence: 99%
“…The motion direction of the envelope depended on the size of the FSR formed by the sensing arm and the reference arm. It did not necessarily coincide with the direction of movement of the [29] 7065 nm/RIU 1.3333-1.3405 1.74 × 10 −5 RIU CRS [30] 4244.44 nm/RIU -1.34 × 10 −5 RIU Cascading the θ-shaped microfiber resonator with a fiber Fabry-Perot interferometer [31] 2460.07 nm/RIU Compared with a single MZI sensor, the sensitivity of the CMZIs sensor based on VE is significantly improved. Table 2 shows the performance comparison between the different sensors.…”
Section: Measurement Of Glucose Concentration Based On Cmzismentioning
confidence: 98%
“…The results shown in the table align with our analysis showing that the silicon platform achieves the highest sensitivity among the three platforms, while silica shows the lowest sensitivity. Note that these are just samples from a number of works [15][16][17][18][19] conducted in this field. Much higher sensitivities have also been achieved but with much more complex designs, for instance, cascaded MRRs.…”
Section: Comparative Studymentioning
confidence: 99%
“…There is a plethora of work conducted in regard to on-chip optical RI sensing and many interesting review articles can be found in the literature [15][16][17][18][19]. On-chip RI sensing can be classified into two main types; interferometer-based and resonance-based devices.…”
Section: Introductionmentioning
confidence: 99%